Pediatric Lupus Presenting as Pulmonary Hypertension, Myocarditis, and Massive Pericardial Effusion in an 11-Year-Old Girl: A Case Report and Literature Review - Chen, Yu-Jhen; Lin, Ying-Jui; Guo, Mindy Ming-Huey (Frontiers in Pediatrics, 2022)
Systemic lupus erythematosus (SLE) is an autoimmune disease which may cause vital organ damage. Although it is not rare for child-onset SLE to have cardiovascular or pulmonary involvement, myocarditis and pulmonary hypertension are infrequent features and can be life-threatening. In this case report, we describe an 11-year-old girl with SLE who initially presented with fulminant myocarditis pulmonary hypertension, and massive pericardial effusion. Initial immunosuppressive therapy with methylprednisolone pulse therapy, IVIG, and finally cyclophosphamide was ultimately successful, with no residual pulmonary hypertension and no recurrence of myocarditis for over three years after the initial episode. Our case highlights the need for clinicians to vigilant of systemic lupus erythematosus as a possible diagnostic entity in pediatric patients with severe myocarditis or pulmonary hypertension. Aggressive immunosuppressive therapy should be strongly considered in such cases, and may lead to good short-term and long-term outcomes.